Efectos de los macronutrientes principales, sobre el desarrollo y rendimiento del cultivo de maíz canguil (Zea mays L.), en la zona de Babahoyo - Aguilar Cortez, Dayanna Jhomaira (2020)
The research was carried out on the farms of the “San Pablo” Farm of the Technical University of Babahoyo, located at Km 7½ of the Babahoyo - Montalvo road, with an altitude of 8 meters above sea level. X coordinates: -1,799621, - Y: 79,473936. The subject to evaluate was: Effects of the main macronutrients, on the development and yield of the cultivation of canguil corn (Zea mays L.). Canguil corn was planted in plots of 20 m2. Seven treatments were performed with three repetitions. The treatments were distributed in a randomized complete block design. For the evaluation of means, the Tukey test at 5% significance was used. During the crop cycle the following were evaluated: plant height to harvest, ear insertion height, stem diameter, leaf area, leaf area index, chlorophyll, agronomic efficiency per nutrient, ear diameter, ear length, ratio dry matter / grain, weight of 1000 grains, grain / tusa ratio, grain yield, economic analysis. The results showed that the best results were not obtained in the control, while in treatment 7 with application Nitrogen 150kg / ha, Phosphorus 27kg / ha, Potassium 102kg / ha, obtaining the best results in the study variables such as the higher crop yield that was 4112.05 kg / ha with a benefit of $ 1795.69.